Project management for mere mortals - Baca, Claudia; Safari eBooks ([United States?] : Addison-Wesley Professional, 2007)
"Project Management for Mere Mortals is a comprehensive video training course that teaches key techniques, using a live case study that covers all five process groups of project management: initiation, planning, execution, monitoring/controlling, and closing."--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Title from resource description page (viewed Feb. 22, 2009).
Electronic reproduction.
Keywords: Project management; Electronic books